2013
DOI: 10.1038/nchem.1667
|View full text |Cite
|
Sign up to set email alerts
|

Detection of different oxidation states of individual manganese porphyrins during their reaction with oxygen at a solid/liquid interface

Abstract: [4][5][6][7] . The majority of these studies use ensemble techniques in solution, such as electrochemistry and absorption, electron paramagnetic resonance and nuclear magnetic resonance spectroscopy. The scanning tunneling microscope (STM) has proven to be a promising tool to study reactions at the molecular level [8][9][10][11][12] , and initial experiments have been reported in which the reactive properties of metal porphyrins were studied on a surface at the single molecule level by STM in ultrahigh vacuum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(86 citation statements)
references
References 43 publications
4
82
0
Order By: Relevance
“…20,60 The highly ordered self-assembly was likely a result of the strong π–π interaction between the HOPG substrate and the aromatic ladder-type backbone. 61,62 These rods under STM showed alternating sections of high and low signal with a periodic length at around 1.27 nm. According to the single crystal structure of 3 and DFT calculations on model oligomers resembling P2 , the feature length of each repeating unit on P2 was close to 1.26 nm, matching well with the experimental results.…”
Section: Resultsmentioning
confidence: 99%
“…20,60 The highly ordered self-assembly was likely a result of the strong π–π interaction between the HOPG substrate and the aromatic ladder-type backbone. 61,62 These rods under STM showed alternating sections of high and low signal with a periodic length at around 1.27 nm. According to the single crystal structure of 3 and DFT calculations on model oligomers resembling P2 , the feature length of each repeating unit on P2 was close to 1.26 nm, matching well with the experimental results.…”
Section: Resultsmentioning
confidence: 99%
“…showed that the catalytic activity of FePc for surface oxidation can be reproducibly switched on or quenched by controlling the FePc local adsorption site, and the FePc–(η 2 ‐O 2 )–Ag coordination complex was imaged by using ultrahigh vacuum (UHV) STM . Furthermore, different oxidation states and oxidation products of individual MnP derivatives have also been investigated by using STM. However, despite the studies of the MP‐catalyzed oxidation reaction in UHV or ambient environment, there are few in situ electrochemical studies about the ORR mechanism at the single‐molecule scale.…”
Section: Figurementioning
confidence: 99%
“…[9][10][11][12][13][14][15] To efficiently design and predict the formationo ft hermodynamically stable molecular ordering formed through self-assembly processes, interplays of various interactions,s uch as molecule-substrate interactions,i ntermoleculari nteraction, [16][17][18][19][20] solvent effects, [21][22][23][24][25] and the balance of enthalpy and entropyt erms, [26][27][28][29] must be taken into account. Various systems employing these interactions, such as chiral assemblies, [21,[30][31][32][33] post-assembly manipulation, [34][35][36][37] and porous networks, [2,17,38] have recentlyb een intensively investigated by many groups.…”
Section: Introductionmentioning
confidence: 99%